Penerapan Rapid Prototyping Dalam Analisis dan Perancangan Sistem Pemasaran dan Pemesanan Properti Pada PT. Singgah Artha Sejahtera - Hidayah, Nurul Hidayah; Alawi, Zakki (Multidisciplinary Applications of Quantum Information Science (Al-Mantiq), 2025)
Digital transformation in the property sector is essential due to the limitations of conventional marketing and ordering methods. PT. Singgah Artha Sejahtera still relies on manual systems that hinder service efficiency and reach. This study aims to analyze and design a web-based property marketing and ordering system using the Rapid Prototyping method. The method was chosen for its iterative nature and ability to quickly produce prototypes while involving users throughout the development process. The stages include needs assessment, interface design, initial system implementation, and usability testing. The result is a functional system that supports property data management, filtered property search, online booking, and transaction reporting. Usability testing indicates the system is user-friendly and enhances user experience. This study contributes to the application of Rapid Prototyping in property information system development and may serve as a reference for other property companies seeking business process digitalization.